Are Religious Experiences Immediate Revelations?: A Study of Pentecostal Hermeneutics - Antombikums, Aku S. (Verbum et ecclesia, 2024)
Religious encounters are essential to every religious tradition in which the worshipper encounters the divine. Although religious experiences have been reported in many religious traditions, they occupy a premium place in Pentecostalism. Given the ontological distinction between humans and the transcendent, the Abrahamic religions speak about revelation, where the divine is revealed to the worshipper. This article explores the Pentecostal understanding of religious experiences, particularly in relation to whether religious experiences are immediate revelations. The article examines prophecies, words of knowledge and testimonies from personal encounters to ascertain whether they constitute immediate revelation. In other words, what is the epistemological relevance of such experiences? Further, if such expressions or personal encounters can be equated to immediate revelation, how should such revelations be understood in the broader context of divine revelation? This article argues that religious experiences are subjective and can only be valid if they do not contradict biblical teachings. Lastly, the article argues that religious encounters in Pentecostalism raise many theological questions and objections because they have been overemphasised, overgeneralised and inform its hermeneutics. Intradisciplinary and/or interdisciplinary implications: The article contributes to the current discussion on discerning divine presence using the methods of analytic theology. The article looks at how Pentecostalism biblicised and appropriated its current spiritual experiences into redemptive history, especially with respect to the outpouring of the Holy Spirit in the book of Acts of the Apostles.